Behavior of foundation piles resisting lateral forces in soft soil - Rusdiansyah,; Ma’ruf, Muhammad Afief; Hidayah, Nurul (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The role of the foundation in construction is crucial. Foundation planning aims to ensure that it can support loads up to a specified safety limit, including the maximum load that may be encountered. The foundation serves as the lower structure that interacts with the soil, providing stability and support for the superstructure. In this study, the analysis focused on the bearing capacity of the pile foundation under lateral forces. The Brinch Hansen method was employed to determine the allowable lateral bearing capacity, while the computer application was used to calculate the lateral deflection. Various pile lengths, such as 20m, 25m, 30m, 34m, and 40m, as well as different dimensions, including circular piles with diameters D30, D35, D40, and square piles measuring 30x30, 35x35, and 40x40, were considered. The analysis revealed that square cross sections exhibited greater allowable lateral bearing capacity compared to circular cross sections. The square sections showed smaller lateral deflection values in comparison to the circular sections.